Interscanner and Intrascanner Comparison of Virtual Unenhanced Attenuation Values Derived From Twin Beam Dual-Energy and Dual-Source, Dual-Energy Computed Tomography. Issue 1 (January 2019) - Obmann, Markus M.; Kelsch, Vanessa; Cosentino, Aurelio; Hofmann, Verena; Boll, Daniel T.; Benz, Matthias R.
Abstract : Objective: The aim of the current study was to evaluate the reliability and comparability of virtual unenhanced (VUE) attenuation values derived from scans of a single-source, dual-energy computed tomography using a split-filter (tbDECT) to a dual-source dual-energy CT (dsDECT). Materials and Methods: In this retrospective study, comparisons for tbDECT and dsDECT were made within and between different dual-energy platforms. For the interscanner comparison, 126 patients were scanned with both scanners within a time interval of 224 ± 180 days; for the intrascanner comparison, another 90 patients were scanned twice with the same scanner within a time interval of 136 ± 140 days. Virtual unenhanced images were processed off of venous phase series. Attenuation values of 7 different tissues were recorded. Disagreement for VUE HU measurements greater than 10 HU between 2 scans was defined as inadequate. Results: The interscanner analysis showed significant difference between tbDE and dsDE VUE CT values ( P < 0.01) for 6 of 7 organs. Percentage of cases that had more than 10 HU difference between tbDE and dsDE for an individual patient ranged between 15% (left kidney) and 62% (spleen). The intrascanner analysis showed no significant difference between repeat scans for both tbDECT and dsDECT ( P > 0.05). However, intrascanner disagreements for the VUE HU measurements greater than 10 HU were recorded in 10% of patients scanned on the tbDECT and 0% of patients scanned on the dsDECT. The organs with the highest portion of greater than 10 HU errors were the liver and the aorta (both 20%). Conclusions: Dual-energy techniques vary in reproducibility of VUE attenuation values. In the current study, tbDECT demonstrated higher variation in VUE HU measurements in comparison to a dsDECT. Virtual unenhanced HU measurements cannot be reliably compared on follow-up CT, if these 2 different dual-energy CT platforms are used. Abstract : Supplemental digital content is available in the text.